Origin of Equisetum: Evolution of horsetails (Equisetales) within the major euphyllophyte clade Sphenopsida. Issue 8 (19th July 2018) - Elgorriaga, Andrés; Escapa, Ignacio H.; Rothwell, Gar W.; Tomescu, Alexandru M. F.; Rubén Cúneo, N.
Abstract : Premise of the Study: Equisetum is the sole living representative of Sphenopsida, a clade with impressive species richness, a long fossil history dating back to the Devonian, and obscure relationships with other living pteridophytes. Based on molecular data, the crown group age of Equisetum is mid‐Paleogene, although fossils with possible crown synapomorphies appear in the Triassic. The most widely circulated hypothesis states that the lineage of Equisetum derives from calamitaceans, but no comprehensive phylogenetic studies support the claim. Using a combined approach, we provide a comprehensive phylogenetic analysis of Equisetales, with special emphasis on the origin of genus Equisetum . Methods: We performed parsimony phylogenetic analyses to address relationships of 43 equisetalean species (15 extant, 28 extinct) using a combination of morphological and molecular characters. Key Results: We recovered Equisetaceae + Neocalamites as sister to Calamitaceae + a clade of Angaran and Gondwanan horsetails, with the four groups forming a clade that is sister to Archaeocalamitaceae. The estimated age for the Equisetum crown group is mid‐Mesozoic. Conclusions: Modern horsetails are not nested within calamitaceans; instead, both groups have explored independent evolutionary trajectories since the Carboniferous. Diverse fossil taxon sampling helps to shed light on the position and relationships of equisetalean lineages, of which only a tiny remnant is present within the extant flora. Understanding these relationships and early character configurations of ancient plant clades as Equisetales provide useful tests of hypotheses about overall phylogenetic relationships of euphyllophytes and foundations for future tests of molecular dates with paleontological data.